Chinese Whispers and the Geopolitics of the Pacific Islands - Wallis J; Powles A (Asia Global Institute, The University of Hong Kong, 2018)
Australia and New Zealand have long viewed the Pacific Islands as part of their sphere of influence. China’s increasing engagement in the region is now throwing that in doubt. Canberra and Wellington must reconfigure their regional strategies to be more inclusive, and recognize Pacific Island states as sovereign actors in their own right.